Identifying a Role of Polysaccharides from Agaricus Blazei Murill in Combating Skin Photoaging: The Effect of Antioxidants on Fibroblast Behavior - Feiqian Di; Wenjing Cheng; Luyao Li; Chunhong Pu; Ruiliang Sun; Jiachan Zhang; Changtao Wang; Meng Li (Fermentation, 2024)
Irradiation with ultraviolet A (UVA) plays an important role in the pathogenesis of skin photoaging since it increases oxidative stress and inflammation in the epidermis. There is an urgent need to screen, investigate, and apply the potential anti-photoaging active ingredients. Agaricus blazei Murill (ABM) polysaccharides have a wide range of promising pharmacological applications. Previous studies have confirmed their antioxidant effect, but whether it has an anti-photoaging effect is unclear. In this study, two ABM polysaccharides (AB-J and AB-K) were obtained to discuss the potential photodamage-protective capacity. The free radical scavenging abilities in vitro, the safety assessment, and their protective effects and mechanisms on UVA-induced human fibroblasts (HSFs) were evaluated. The intracellular antioxidant enzyme levels and extracellular matrix proteins, such as COL-I and ELN, were significantly accelerated, and metalloproteinases (MMP-1, and MMP-9) were decreased by AB-J and AB-K. The Keap-1-Nrf2/ARE signaling pathway was activated, thus inducing the upregulated expression of downstream genes (Ho-1 and Nqo-1). The suppression of P38 and Jnk1 by AB-J and AB-K was speculated to be the inducer of the activation of the Keap-1-Nrf2/ARE signaling pathway. Owing to the excellent exhibition of AB-J, its safety assessment and the structural characterization are discussed further.